TikTok Content Analysis as a Political Campaign Medium for the 2024 Presidential Candidates - Adam, Ryan (Universitas Islam Negeri Raden Intan Lampung, 2023)
TikTok has the potential to be a powerful tool for political campaigns, especially for searching young voters. Issues related to identity politics, tolerance, freedom of religion, and protection of human rights will continue to be an important concern in the presidential election. A political campaign refers to the organized efforts undertaken by candidates, political parties, or advocacy groups to influence public opinion, garner support, and secure votes during an election or for a specific political cause. This study aims to analyze the content shared on TikTok by presidential candidates, evaluate its effectiveness in reaching and engaging voters. This research will use qualitative approach. These specific objectives include analyzing political messages, assessing visual communications, evaluating campaign strategies, understanding user interactions, comparative analysis within the TikTok platform. By conducting a comprehensive content analysis of TikTok as a political campaign medium. This research tries to provide an overview of the effectiveness of using TikTok for political communication. These findings will contribute to be a better understanding of TikTok’s potential as a platform to engage and mobilize voters in the context of the 2024 presidential election.